2006
DOI: 10.1002/jmri.20725
|View full text |Cite
|
Sign up to set email alerts
|

Displacement of the facial nerve course by vestibular schwannoma: Preoperative visualization using diffusion tensor tractography

Abstract: Purpose: To preoperatively visualize the course of the facial nerve, which is displaced by vestibular schwannoma, using diffusion tensor (DT) tractography, and to evaluate the agreement with surgical findings. Materials and Methods:The subjects were eight patients with vestibular schwannoma who had undergone removal surgery. DT MR images were obtained and tracts that were considered to represent the facial nerve were constructed. We assessed the success rate for tract construction and evaluated the agreement b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(61 citation statements)
references
References 10 publications
0
59
0
2
Order By: Relevance
“…The applicability of tractography to the study of cranial nerves is novel and few studies have been reported in this area [22], [23]. We recently demonstrated that tractography can be used to delineate the course of the cranial nerves, and that significant information with respect to the DTI parameters can be obtained [19], [24].…”
Section: Discussionmentioning
confidence: 99%
“…The applicability of tractography to the study of cranial nerves is novel and few studies have been reported in this area [22], [23]. We recently demonstrated that tractography can be used to delineate the course of the cranial nerves, and that significant information with respect to the DTI parameters can be obtained [19], [24].…”
Section: Discussionmentioning
confidence: 99%
“…One of the major applications of WMT in skull base surgery is the preoperative identification of the facial nerve (FN) position, in patients harboring large vestibular schwannomas. We reviewed the existing literature comparing tractography predicted FN position with intraoperative findings (Table 6) (Gerganov et al, 2011, Song et al, 2016, Taoka et al, 2006, Wei et al, 2015, Zhang et al, 2013). FN tractography reconstruction was possible in 93% of the cases (71/76).…”
Section: Infratentorialmentioning
confidence: 99%
“…Both the facial nerve and the schwannoma have similar signal intensities, and larger tumors cause thinning of the facial nerve, making the nerve even more difficult to identify. Additionally, there is typically no intervening cerebrospinal fluid between the schwannoma and the facial nerve [2]. In these cases, diffusion tensor (DT) tractography may be useful for assessing facial nerve course and displacement.…”
Section: Imaging Techniques For the Evaluation Of The Facial Nervementioning
confidence: 99%
“…Diffusion tensor (DT) tractography, which uses MRI to make three-dimensional (3D) reconstructions of the facial nerve, has recently been developed. This technique has been shown to be potentially useful in the identification displacement of cranial nerve fibers by vestibular schwannomas [2]. In all cases, choice of the imaging modality utilized should be determined by specifics of the patient's symptoms and the differential diagnosis.…”
Section: Introductionmentioning
confidence: 99%